2016
DOI: 10.1515/pjct-2016-0014
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of CO2 reaction with CaO by a modified random pore model

Abstract: In this work, a modifi ed random pore model was developed to study the kinetics of the carbonation reaction of CaO. Pore size distributions of the CaO pellets were measured by nitrogen adsorption and mercury porosimetry methods. The experiments were carried out in a thermogravimeter at different isothermal temperatures and CO 2 partial pressures. A fractional concentration dependency function showed the best accuracy for predicting the intrinsic rate of reaction. The activation energy was determined as 11 kcal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
1
5
0
1
Order By: Relevance
“…This confirms that a complex model is not necessarily required to obtain reaction kinetics in this instance. This values also agrees well with Nouri and Ebrahim 34 (46 kJ mol -1 ) as well as Dedman and Owen 35 (39 kJ mol -1 ). However, this activation energy differs from the activation energies obtained by other authors.…”
Section: Temperaturesupporting
confidence: 91%
“…This confirms that a complex model is not necessarily required to obtain reaction kinetics in this instance. This values also agrees well with Nouri and Ebrahim 34 (46 kJ mol -1 ) as well as Dedman and Owen 35 (39 kJ mol -1 ). However, this activation energy differs from the activation energies obtained by other authors.…”
Section: Temperaturesupporting
confidence: 91%
“…A further study obtained the kinetic parameters under recarbonation conditions [101]. A simplified RPM was used by Nouri et al to model carbonation of limestone [102], which showed a similar relationship between reaction order and pCO 2 to Bhatia and Perlmutter [86], although E a in the kinetic control region was larger(~47 kJ mol −1 ). Values of E a in the diffusion region were calculated to be~140 kJ mol −1 [102].…”
Section: Pore Models Homogeneous Particle Models and Rate Equation Tmentioning
confidence: 99%
“…There is some disagreement regarding the reaction order for the kinetic control region. Some studies find the reaction to be F1 up to a pCO 2 of 10 kPa [59,86,102]. However, Grasa et al report that the carbonation reaction is F1 up to 100 kPa, before transitioning to F0 at higher CO 2 partial pressures [35] For diffusion, E a values range between~100 [57] and~270 kJ mol −1 [57] for CaO and natural limestones.…”
Section: Comparison Of Carbonation Kinetic Analysismentioning
confidence: 99%
“…For the initial kinetic control region of carbonation, typical values of E a are 19-29 kJ mol −1 in synthetic CaO or natural lime [30], although slightly larger values (i.e., [39][40][41][42][43][44][45][46] [38,39] and 72 kJ mol −1 [37]) have been reported. In the kinetic control region, E a has been reported to be independent of material properties and morphology (although variation in kinetic parameters for synthetic CaO and natural lime may suggest otherwise [30]), while morphological effects have a greater influence in the diffusion control region, leading to a greater disparity in diffusion activation energies [28].…”
Section: Introductionmentioning
confidence: 98%